Tinjauan terhadap Praktik Kedokteran dan Kesehatan Berdasarkan Prinsip Etika Confidentiality yang Berpedoman terhadap Hukum Kesehatan - Handijani, Jatri; Nugroho, Meysita Arum (Syntax Literate, 2023)
This study aims to obtain information and analyze laws regarding medical and health practices based on the principles of health ethics of confidentiality that are guided by health laws. By using the approach method in this study is a normative juridical approach. The formulation of the problem in this study is how is the practice of medicine and health based on the principles of health ethics of confidentiality guided by health law? and How is the Implementation of Medical and Health Practices that Handle Patients in Maintaining Any Information Data Owned from Patients? The most profound thing about the doctor-patient relationship is mutual trust. Patients as parties who need help believe that doctors can cure their illness. Meanwhile, the doctor also believes that the patient has provided correct information about his illness and he will comply with all the doctor's instructions. The Principle of Confidentiality Ethics is one of the ethical codes of professionalism in health law. Understanding based on the confidentiality of patient data must be treated confidentially. Patient medical data is expressly prohibited from being known by people who do not have legal access.